The characteristics and potential transport trajectory of epimicroplastic red tide species in the Taiwan Strait - Peng, Conghui; Wang, Kang; Lin, Hui; Chen, Shunyang; Dong, Xu; Gao, Yahui; Chen, Baohong; Kuang, Fangfang (Frontiers in Marine Science, 2025)
Due to the carrier’s role of microplastics, attached microalgae may be transported further, posing a threat to marine ecosystems, especially those red tide species. By combining the investigated results of Dongshan Bay and Quanzhou Bay with the simulation of transport trajectories using the Lagrangian particle tracking model, this study systematically investigated the characteristics and transport trajectories of epimicroplastic red tide species. Based on the investigations of Dongshan Bay and Quanzhou Bay respectively in summer of 2022, the characteristics of epimicroplastic red tide species were learned. Results showed that totally 13 red tide species were found in two bays, with 6 species in Dinophyta, 5 species in Diatom, 1 species in Ochrophyta and 1 species in Cyanophyta respectively. Also, the potential transport trajectories of epimicroplastic species were simulated to study their effect to the ecological environment of the surrounding waters. According to the simulated transport trajectories, those species could be transported further by microplastics while some particles would be obstructed during these three-month processes. During the transport processes, epimicroplastic red tide species from two bays would influence three provinces, which have high records of red tide outbreak in China. This study firstly combined models to investigate the potential transport trajectory of epimicroplastic red tide species, providing insights into the mechanisms of red tide outbreak.